UJI EFEK ANTIFERTILITAS EKSTRAK METANOL KULIT KAYU DURIAN (Durio zibethinus Murr) PADA KEHAMILAN AWAL MENCIT (Mus musculus L) - Rusmiati Rusmiati (Universitas Lambung Mangkurat, 2009)
The purpose of this study is to determine antifertility effects from durian tree bark extract on early pregnancy of mice. Twelve pregnant mice were divided using split plot design with treatments consisted of control (distilled water), extract concentration 10% w / v, 15% w / v and 20% w / v with n = 3. Extract was given orally to mice 0.5 mL per day, every 25-30 mg of BB for 6 days. At seven days of pregnancy, mice were dissected for ovaries taken and made the histological preparation with paraffin and HE staining method. The collecting of the uterus of mice was done to observe number of implantation. The data which used in this study were the number of corpus luteum on the ovary and the number of implantation in the uterus. Data were analyzed using ANOVA (α = 5%), presented in the mean, standard deviation and percentage comparisons. The results showed that the methanol extract did not affect at early pregnancy of mice, but causes the appearance of teratogenic effects of early resorption at the site of implantation in the treatment of concentration 20% w / v.